The extent of labor regulation on production descentralization - Mejía Madrid, Renato (2014)
Employment decentralization is a newly emerging phenomenon. Nowadays, many companies delegate the work to others through a decentralization of production, thus affecting the traditional view of labor relations. This has been picked up by Labor Law which has regulated labor relations arising from this decentralized production.In this article, and in the light of doctrine and the jurisprudence of the Peruvian Supreme Court, the author develops the concepts of outsourcing and job placement, as well as the requirements to which they are validly given.